The Effect Analysis of Braden Scale on Pressure Ulcer in Community-Dwelling Older Adults - Desri Kristina Silalahi; Husneni Mukhtar; Sheizi Prista Sari; Eka Afrima Sari; Dandi Trianta Barus (Bina Nusantara University, 2020)
The research aimed to analyze the Braden Scale on the incidence of compressive wounds in elderly people who lived in homes, whether they were or not under the supervision of health workers. The research was analytic with a cross-sectional study. With the purposive sampling technique, the data collection was carried out from several areas in Bandung from October to November 2017. Moreover, the analysis used was multiple regression to see the effect of the Braden Scale on pressure ulcers. The multiple linear regression model was also tested. The results show that 48,22% of pressure ulcer factors can be influenced by sensory perception, humidity, activity, mobility, nutrition, and friction. Sensory perception, activity and friction have significant influence on incidence of pressure ulcers. Meanwhile, the humidity, mobility, and nutrition do not significantly influence it.